Sistem Informasi Kasir Terintegrasi Perangkat Jaringan Mikrotik pada Angkringan Kula Kita - Aristi, Nina Mia; Ridha, M.Najamudin; Zulfahri, Aidil Fajar; Ningrum, Eny Novita; Sabella, Billy (JITU, 2026)
Angkringan Kula Kita, located in Tanah Laut, provides free Wi-Fi for its customers. However, in practice, Wi-Fi access is still provided without an integrated management system. Wi-Fi usernames and passwords are shared publicly without maximum time or connected devices limit, so it is often used by customers who are not making transactions, which has an impact on reducing internet connection speeds for other customers who are enjoying the service on site. A Web-Based Cashier Information System Integrated with Mikrotik Network Devices is designed to address these needs, especially in managing sales transactions and customer Wi-Fi network access automatically. This system was built with the aim of simplifying the process of recording transactions, managing network access based on transaction values, and preparing structured sales reports. The system development method uses the waterfall model. The database design is carried out using ERD, while system modeling uses UML. This system was developed with the CodeIgniter 4 Framework using the PHP programming language and MySQL database. There are three types of user access rights, namely Admin, Owner, and Employee.. Testing was carried out using Black Box Testing and User Acceptance Testing with a test result percentage of 99% stating that the system functionality was running well.